(untitled) (Bangladesh Journal of Neurosurgery, 2024)
Sphenoorbital meningiomas (SOM) constitutes 9% of all intracranial meningiomas and are originated from sphenoid wing dura. They are also called en plaque meningioma. They cause hyperostosis of involved bone and their soft tissue growth may spread the orbit, the infratemporal fossa, and the temporal fossa. Most patients with SOM are middle- aged women and most commonly presents with unilateral, nonpulsating, progressive proptosis. Recently a woman with unilateral progressive proptosis from a remote area of Bangladesh presented to us with blindness of her left eye due to diagnostic delay. After thorough evaluation and imaging studies, she was diagnosed with a large spheno-orbital meningioma with extensive bony involvement of skull base and orbit. Objective: This report highlights the necessity of creating awareness among optometrists, undergraduate medical students as well as and ophthalmologists who are practicing in remote areas of Bangladesh about clinical presentation of sphenoorbital meningiomas which is a benign lesion but may be a cause of unilateral blindness if remain undiagnosed for long Bang. J Neurosurgery 2023; 13(1): 51-54